Electrochemical performance of high and medium entropy oxides for lithium batteries - Fracchia, M.; Callegari, D.; Coduri, M.; Anselmi-Tamburini, U.; Manzoli, M.; Quartarone, E.; Ghigna, P. (Frontiers in Energy Research, 2022)
Various high and medium entropy oxides with the rock salt structure have been prepared and studied as anodes for lithium batteries. All the systems have complex reaction mechanisms involving conversion reactions. The capacity and reduction potentials depend on the number of component and microstructure of the initial materials. However, the dependence is difficult to be rationalised based on simple stability logic. The implication of our findings are discussed in this paper in the wider context of the science of high entropy materials.